Increased production of cellulosic sugars from lignocellulosic materials - Alhammad, Alaa (My University, 2018)
Renewable energy is energy that is regenerated naturally for infinite time. Renewable energy can be categorized into solar, hydro, wind, geothermal, and biomass. Biomass is an organic material such as agricultural, forest residues, energy crops (Jatropha, miscanthus, switch grass and etc) and algae. The current study focusing on biomass based renewable and sustainable energy production from lignocelluloses biomass. As the name suggest lignocellulosic biomass is made up of lignin, cellulose and hemicellulose and the cellulose, hemicellulose are made up of polymerized C5 and C6 sugars such as glucose, xylose, arabinose, mannose, and galactose. Due to the complex nature of lignocellulosic biomass, the sugars present in plant biomass are not readily accessible for production of biofuels and biochemicals. Hence, a pretreatment of lignocellulosic biomass to loosen up the lignocellulosic matrix, followed by a hydrolysis process with enzymes or acids is necessary to obtain a fermentable stream of monomeric sugars. The objectives of this study were to: 1) investigate the enzymatic production of fermentable sugars (glucose) from underutilized, low-cost lignocellulosic biomass such as poplar wood, and 2) examine factors that can enhance the efficiency of enzymatic hydrolysis leading to higher glucose yields and lower production costs. A two-stage steam-exploded poplar wood biomass was used as substrate in this work. Initially the effect of inhibitors that generally form during high temperature pretreatment was evaluated by washing the biomass with distilled water. There were no significant improvement in hydrolysis yield was obtained, perhaps significant reduction in sugar yield was noticed after 96h of hydrolysis. Therefore unwashed biomass was used in all our studies. There after the effect of original pH (3.0) of pretreated poplar pulp and optimum pH (5.0) of cellulase on hydrolysis yield was studied. Interestingly the commercial cellulase preparation was active at pH 3.0, however pH 5.0 was chosen for further studies due to slightly higher sugar yield. To overcome the low hydrolysis efficiency, critical parameters such as enzyme loading, substrate consistency, hydrolysis time, and substrate recycling were evaluated. Based on the results, 5% enzyme loading and 5% substrate consistency were found to be optimal. Substrate recycling could possibly reduce the enzyme usage in successive hydrolysis cycling. A 50% reduction in sugar yield was observed after 2 successive recycling of substrate, hence adding fresh enzyme at low concentration was recommended. Further, the effect of different surfactants on hydrolysis was studied. Compared to the control (without surfactant), 1% PEG4000 produced highest sugar yield of 58.5% at 5% substrate consistency and 5% enzyme loading. Compared to PEG4000, other surfactants studied (PEG8000, Tween 20, and TritonX100) improved hydrolysis yield to a lower extent. Therefore, addition of surfactant can enhance the hydrolysis efficiency of enzymes. The most likely mechanism for this effect is believed to be by a surfactant-facilitated blocking of the non-productive sites on lignin, which results in increase in the concentration of free enzymes available for enzymatic hydrolysis.
Keywords: Lignocellulosic biomass; Biomass energy conversion; Enzymatic hydrolysis; Biomass production; Renewable energy